EVALUATION OF DISPERSED PARTICLE CONTENT IN EXHAUST GAS OF DIESEL ENGINE - G. M. Kuharonak; V. I. Berazun (Наука и техника)
Pollution of an atmosphere due to hazardous substances emissions deteriorates ecological environment in the world. Exhaust gases of diesel engines are considered as one of the main environmental pollutants. At the moment it is not possible to determine rate and limits of threshold level of air pollution which do not affect human health. The paper considers current issues pertaining to regulation and control over dispersed particles. The most convenient measuring methods for investigations are those which provide the opportunity to obtain immediate results. However, from the legislative point of view, a gravimetric investigation method is a legitimate one which requires compliance with certain procedures of adjustments and calculations. The method presupposes availability of complicated system for sample dilution and its adjustment must include temperature and kinetic parameters of the measured flow. In order to ensure measuring accuracy and results reproducibility filter loading should be in a regulated range and dilution parameters should be chosen according to not only engine type but also according to its emissions rate. Methods for evaluation of a hot exhaust gas sample is characterized by higher response and the results correlate with indices of combustion efficiency. However, such approach does not account for a number of processes that take place during gas cooling in the environment. Therefore, in this case, measuring results are to be evaluated within certain boundary conditions with respect to the object of investigations. Difficulty in achievement of modern ecologocal standards is substantiated by complicated fractional composition and multiple stage process in formation of hazardous components. The paper presents calculated dependences between particles and smokiness and contains a comparative analysis. Methods for measurement and investigations of dispersed particles have analyzed on the basis of the results obtainesd during engine tests at various values of fuel supply parameters (injection pressure and timing advance angle of fuel injection).